Evaluating China's primary healthcare services' efficiency and spatial correlation: a three-stage DEA-Malmquist model - Huang, Rui; Li, Wan; Shi, Baoguo; Su, Hao; Hao, Jing; Zhao, Chuanjun; Chai, Juhong (Frontiers in Public Health, 2024)
Enhancing the efficiency of primary healthcare services is essential for a populous and developing nation like China. This study employs a three-stage DEA-Malmquist model to assess the efficiency of primary healthcare services across 31 provincial units in mainland China from 2012 to 2020. Additionally, it examines the spatial correlation of efficiency distribution using the Moran Index. The findings reveal that the efficiency of primary healthcare services in China is generally suboptimal with a noticeable declining trend, highlighting significant potential for improvement in both pure technical efficiency and scale efficiency. There is a pronounced efficiency gap among provinces, yet a positive spatial correlation is evident. Regionally, efficiency ranks in the order of East > Central > West. Factors such as GDP per capita and population density positively influence efficiency enhancements, while urbanization levels and government health expenditures appear to have a detrimental impact. The application of the three-stage DEA-Malmquist model and the Moran Index not only expands the methodological framework for researching primary healthcare service efficiency but also provides scientifically valuable insights for enhancing the efficiency of primary healthcare services in China and other developing nations.